Carbonylative Acetylation of Heterocycles. Issue 2 (3rd January 2020) - Zhang, Youcan; Yin, Zhiping; Wu, Xiao‐Feng
Abstract : Herein, a new procedure for the carbonylative acetylation of heterocycles has been developed. In this process, organic peroxide acts as the methyl source. Various heterocycles were transformed into the corresponding methyl heterocyclic ketones in moderate to good yields. Abstract : A new procedure for the carbonylative acetylation of heterocycles has been developed. In this process, organic peroxide acts as the methyl source, various heterocycles were transformed into the corresponding methyl heterocyclic ketones in moderate to good yields.